Intestinal Transit in Early Moderate Parkinson’s Disease Correlates with Probable RBD: Subclinical Esophageal Dysmotility Does Not Correlate - Casper Skjærbæk; Karoline Knudsen; Martin Kinnerup; Kim Vang Hansen; Per Borghammer (Parkinson's Disease)
Background. Nonmotor symptoms, including constipation and dysphagia, are very common in Parkinson’s disease (PD) and Lewy pathology is widespread in the gastrointestinal tract, particularly in the lower esophagus. Constipation and REM sleep behavior disorder (RBD) may present prior to clinical diagnosis. Yet, little is known about esophageal dysfunction and its connection to constipation in early PD. Objective. This study aimed to investigate esophageal and colonic transit in early moderate PD and to study correlations between symptoms and objective measures. Methods. Thirty early moderate PD patients and 28 healthy controls (HC) were included in this cross-sectional study. Esophageal transit times were determined by esophageal scintigraphy and colonic transit times by CT after radio-opaque marker ingestion. Olfaction tests, clinical evaluation, and nonmotor questionnaires were also performed. Results. Distal esophageal transit times and colonic transit times were both significantly prolonged in the PD group compared to HC (p<0.05 andp<0.01, respectively) and a moderate-strong positive correlation was found between colonic transit time (CTT) and RBDSQ score (r = 0.61,p<0.001). Significant correlations were also found between CTT and SCOPA-AUT scores as well as between CTT and ROME III functional constipation scores. Conclusion. Colonic transit correlates with probable RBD and is more severely prolonged in early moderate PD than is the distal esophageal transit time.